Pollinator probing preference and switching mode-mediated self-interference within a monoecious plant significantly reduced reproductive fitness - Wu, Bi-Xian; Ma, Li-Na; Xia, Nan; Wang, Hao; Cao, Guo-Xing (Frontiers in Plant Science, 2023)
Monoecy is usually interpreted as an important evolutionary route of the plant sexual system from hermaphroditism to dioecy. This floral mechanism can effectively reduce self-interference during the reproductive process, and the services provided by pollinators may play an essential role in monoecious species, but relevant research is still lacking. Thus, we aimed to detect whether monoecious plants can effectively avoid self-interference and promote the evolution of monoecy under the service of pollinators. Here, we successfully performed manipulation experiments to test self-compatibility, pollinator behavior, and self-interference between male and female functions in Akebia trifoliata, a typical monoecious species. We demonstrated that experimental self-pollination did not yield any fruit, and supplemental pollination significantly increased fruit set and fruit weight compared with natural pollination, suggesting that this species is completely self-incompatible and experiences strong pollen limitation. Simultaneous self- and cross-pollination and self-pollination prior to cross-pollination significantly reduced reproductive fitness, but self-pollination after cross-pollination did not, indicating the existence of self-interference in this plant. Moreover, both the male flower probing preference and switching modes within inflorescences by pollinators successfully reinforced self-interference, and were also responsible for decreasing reproductive fitness in A. trifoliata. In summary, the pollinator-mediated self-interference reduced selfing significantly, which provides potential dynamics for the maintenance and evolution of monoecy.